Exploring Linguistics Diversity: Comparing Pandhalungan and Madurese Variations - Evi Khoirun Nisa; Evynurul Laily Zen; Nurenzia Yannuar (RETORIKA: Jurnal Ilmu Bahasa, 2024)
Ethnic enclaves and interethnic marriage can contribute to social dialect. The Madurese ethnic enclave on Java Island and Pandhalungan is one of the most intriguing examples. This study investigates the comparison between Madurese and Pandhalungan in Madurese language variations. This study aims to identify the differences between Madurese and Padhalungan in Madurese language variations. This study purposes to reveal the similarities and differences in speech levels between native Madurese and Pandhalungan speakers, as well as how the use of Madurese language variations varies across different social settings. This study employed a qualitative approach with a descriptive qualitative design. The data collected through a semi-structured interview. This study used purposive sampling to select the respondents as the data source. The study's sample consisted of six undergraduate students majoring in English education in Sociolinguistics for the ELT course. These students represented four native Madura regions: Bangkalan, Sumenep, Sampang, and Pamekasan, with ages ranging from twenty to twenty-five years old. Additionally, two students from Pandhalungan, specifically Probolinggo, whose parents are Madurese and Javanese, were included. The finding shows that Madurese language variations can be found in dialect, speech level, and vocabulary. These different speech levels leaded to the use of different vocabularies based on the setting, age, and social role of the people in the communication. The dialect in Padhalungan is distinct, yet the sounds are nearly identical across all regions. In Madura, a distinct dialect is heard in every region. However, Madurese natives and Pandhalungan share the same level of Madurese speech